2019
DOI: 10.3748/wjg.v25.i38.5838
|View full text |Cite
|
Sign up to set email alerts
|

Nomogram to predict prolonged postoperative ileus after gastrectomy in gastric cancer

Abstract: BACKGROUNDProlonged postoperative ileus (PPOI) is one of the common complications in gastric cancer patients who underwent gastrectomy. Evidence on the predictors of PPOI after gastrectomy is limited and few prediction models of nomogram are used to estimate the risk of PPOI. We hypothesized that a predictive nomogram can be used for clinical risk estimation of PPOI in gastric cancer patients.AIMTo investigate the risk factors for PPOI and establish a nomogram for clinical risk estimation.METHODSBetween June 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…We excluded the secondary PPOI resulting from postoperative anastomotic leakage, intraabdominal abscess and peritonitis [ 23 , 24 ]. The use of opioid analgesics in the postoperative period was identified as an increased risk for PPOI [ 25 , 26 ]. However, this information is not available pre/intraoperative and cannot contribute to the prediction model.…”
Section: Discussionmentioning
confidence: 99%
“…We excluded the secondary PPOI resulting from postoperative anastomotic leakage, intraabdominal abscess and peritonitis [ 23 , 24 ]. The use of opioid analgesics in the postoperative period was identified as an increased risk for PPOI [ 25 , 26 ]. However, this information is not available pre/intraoperative and cannot contribute to the prediction model.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that patients with the same cancer stage often have disparate clinical course and varied clinical outcome. Recently, efforts have been made to assist and improve the AJCC staging system by integrating other additional characteristics 46 48 . There is urgent need for a clinical prognosis tool that is not only reliable and accurate but also practical and intuitive and it gives rise to nomogram, an mathematical scoring system 49 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a single-institution retrospective cohort study looking at patients who underwent partial colectomy due to colon cancer in 2008-2015 showed that incidence of POI after partial colectomy is around 17-27% [8]. Liang et al showed that in his study, among 203 patients that underwent gastrectomy for cancer between 2017 and 2018, around 19% of the patients developed POI [9]. Our incidence of 8.61% is significantly lower than shown in these studies most likely due to the fact that we excluded cases that involved resection of bowel.…”
Section: Discussionmentioning
confidence: 99%